The Economics of Innovation Ecosystems in Indonesia: Policy, Entrepreneurship, and inclusive Growth: Ekonomi Ekosistem Inovasi di Indonesia: Kebijakan, Kewirausahaan, dan Pertumbuhan Inklusif - M. Andika Yuda Pratama (Journal of State Economic Research, 2025)
Innovation ecosystems are pivotal for economic growth and competitiveness, especially in emerging economies where entrepreneurship underpins employment and inclusion. Indonesia’s digital economy has expanded rapidly, driven by MSMEs, startups, and fintech platforms, yet structural impediments persist. This study investigates how policy and entrepreneurship shape Indonesia’s innovation ecosystem and foster inclusive growth. Employing a qualitative design, policy content analysis was combined with secondary data from RPJMN, OJK, BI, Kominfo, Kemenkop UKM, BPS, Startup Ranking, Katadata, and the World Bank. Findings reveal that flagship initiatives Making Indonesia 4.0 and the National Financial Inclusion Strategy provide an essential foundation but suffer from institutional incoherence, financing gaps for MSMEs, and uneven digital literacy. These deficiencies undermine the ecosystem’s capacity to deliver broad-based benefits. To unlock its full potential, Indonesia requires enhanced policy coordination, incentives targeted at inclusive startups, expanded digital skills training, and reinforced Triple Helix collaboration among government, industry, and academia. Such integrated strategies are critical for translating digital transformation into sustainable, inclusive development and inform both policymakers and practitioners.